The case of the neonate vs. LMIC medical academia—a jury-style systematic review of 32 years of literature without significant mortality reduction - Amadi, Hippolite O.; Abioye, Ifeoluwa O.; Ugbolue, Ukadike C.; Ekpenyong, Rhoda-Dara; Ekwem, Nnamdi F.; Nwaneri, Ogechi J.; Dike, Chidiebere (Frontiers in Pediatrics, 2024)
Results -Summation of the results showed that 19 out of 4,286 publications were assessed to possess the potential strategies or intervention to reduce neonatal mortality. Fourteen were fully developed but not appropriately scaled-up across the country, hence, denying neonates proper access to these interventions.Conclusion -Nigeria may already have the required game-changing ideas to strategically scale up across the nation to accelerate neonatal survival. Therefore, the LMIC healthcare systems may have to look inwards to strengthen what they already possess.